NILAI TUKAR DAN HARGA SAHAM DI INDONESIA - Muhammad Ilhamsyah Siregar; Taufq Carnegie Dawood; Fakhruddin Fakhruddin; Cut Zakia Rizki; Fitriyani Fitriyani; M. Ridha Siregar; Wahyu Hidayat (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
Abstract The main study of research is to analyze the effect of changes in exchange rates of rupiah against share price in Indonesia. This research employed ARDL model and utilized monthly data for the variables of share price, nominal exchange rate, money supply and GDP. Data is generated from Bank Indonesia and Federal Reserve Economic Data webpage (FRED) from 2008 to 2017. The study results found a negative relationship between the exchange rate and stock price. It found convincing evidence that there is no two-way relationship between both parameters. But there is a positive relationship on other variables such as money supply and GDP during this period. On the basis of the research results obtained its current status, Bank Indonesia is recommended as monetary authority and OJK as capital market regulator must be more prudent in coordinating and cooperating to put together policies and strategies to maintain stable monetary policies to prevent unexpected external shocks which would eventually hit the capital market.